PENINGKATAN PRESTASI BELAJAR IPA TENTANG PERTUMBUHAN TUMBUHAN MELALUI METODE EKSPERIMEN - Wiwik Mardiningsih (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
The study aimed to describe (1) the improvement of Science learning achievement about The growing of Plant through Experimental Method, and (2) The implementation of Experimental method on the material of the Growing of Plant at the first graders of the second state elementary school Kranji, Lamongan. The study was done using classroom action research which is divided into two cycles. Each cycle consisted of four phases, those are remidial planning, (2) remidial action, (3) observation, and (4) reflection. The study was done at the second state elementary school Kranji, Tepanas – Kranji village, Paciran District, Lamongan Regency with the remidial subject 11 students in the low class. From the result could be concluded that the implementation of experimental method can improve the Science learning achievement about the growing of plant at the first graders of the second state elementary school Kranji, Tepanas, Kranji Village, Paciran District, Lamongan Regency.